1942
DOI: 10.1021/ie50392a006
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Sulfur Dioxide as Solvent Medium for Chemical Reactions

Abstract: OtTuOOi forms. This compound was reported by Ollard (14) and has since been observed by Kasper (8) and the author. In view of the ease with which complex chromichromates form, even in highly acid solution, it is concluded that in chromic dichromate (and, to a lesser extent, in aluminum dichromate) solutions, there exists a progressive hydrolysis in which the two chromate complexes described above form from the dichromate complex. In complete accord with this hypothesis is the low pH at equilibrium of chromic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Liquid sulfur dioxide has been employed as a solvent for the sulfonation of benzene (256). These authors concluded that the economically most attractive processes involve sulfonation of benzene with gaseous sulfur trioxide, or benzene vapors with sulfuric acid, in a continuous manner.…”
Section: Direct Sulfonationmentioning
confidence: 99%
“…Liquid sulfur dioxide has been employed as a solvent for the sulfonation of benzene (256). These authors concluded that the economically most attractive processes involve sulfonation of benzene with gaseous sulfur trioxide, or benzene vapors with sulfuric acid, in a continuous manner.…”
Section: Direct Sulfonationmentioning
confidence: 99%
“…The latter approach is used on industrial scale, where processes dealing with a recirculation of SO 2 in a closed contour are well known. Since the first report by Walden at the beginning of the 20th century [40], a variety of Lewis acid-mediated chemical transformations [41][42][43][44][45], especially those with carbenium ion intermediates [46][47][48][49][50][51][52][53][54][55][56], have benefited from the use of liquid SO 2 as the reaction medium. To the best of our knowledge, there has been only one example where liquid SO 2 has been applied as the glycosylation medium to stabilize the oxocarbenium ion formed from glycosyl perchlorate that is generated in situ from glycosyl chloride and AgClO 4 [56].…”
Section: Introductionmentioning
confidence: 99%
“…tion into multiple bonds. [7,8] Consequently, SO 2 was also described as a useful molecule to establish C-C bonds, [9] which is generally one of the key targets in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…As these salts are predominant in general inorganic chemistry, also applications within organic chemistry were established. Sulfur dioxide can be used in a large variety of reactions which allow functionalization due to SO 2 insertion into multiple bonds , . Consequently, SO 2 was also described as a useful molecule to establish C–C bonds, which is generally one of the key targets in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%